A Northwest Semitic Curse Formula: The Sefire Treaty and Deuteronomy 28 - Ramos, Melissa D. (Zeitschrift für die alttestamentliche Wissenschaft, 2016)
An examination of Aramaic curses from the Iron Age and of two texts from biblical law demonstrates striking and robust parallels in thematic content, vocabulary, and syntactical formulation. The curses are all patterned according to a consistent syntactical formula (termed the Northwest Semitic Curse Formula) that governs the order of the presentation of the elements within each line. Thus, the formula shapes both the content of the curse and the order in which the various syntax pieces are given. Furthermore, the geographic distance between these inscriptional exemplars of this curse formula demonstrates broad diffusion of Aramaic curses during the Iron Period and especially during the mid-eighth to the early seventh centuries BCE. These parallel imprecations suggest that a shared tradition of formulaic curse language was part of the training of Aramaic-language scribes and practitioners from the Neo-Assyrian Empire who were sent to peripheral states to facilitate administration.